STRATEGIES TO PREVENT AND COMBAT OBESITY AT YOUR WORKPLACE - Fadillah Ismail, (Journal of Islamic, Social, Economics and Development, 2022)
Obesity is a worrying health condition as it can cause various health complications that affect the quality of life of individuals. Malaysia is the highest ranked country in Asia in the context of individuals with obesity and overweight. This will not only affect the lives of the individuals diagnosed, but the country as well. To enhance more about contemporary issues in combating obesity in the workplace, this paper aims to propose a new index entitling the modern comme il faut well-being intervention by taking account of the significance, impacts and challenges to implementing the strategies accordingly. Since employment accounts for the majority of an adult's hours and days in their lifetimes, employers play a crucial role to build an environmental culture of health at the workplace. Therefore, the organization should plan some strategies that can be suitable for everyone workout, either facilities or rewards if the employee maintains a healthy body weight. By maintaining a good physical image of the employee, this will affect the organization's reputation from the public's or customer's valuation.